2014
DOI: 10.5935/1678-9741.20140027
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Expression of the Left Coronary Artery in Pigs. An approach in relation to human heart.

Abstract: 215Rev Bras Cir Cardiovasc | Braz J Cardiovasc Surg Rev Bras Cir Cardiovasc 2014;29(2):214-20Gómez FA & Ballesteros LE -Morphologic expression of the left coronary artery in pigs. An approach in relation to human heart LCA in pigs have been conducted with small samples and are limited to qualitative descriptions [2,3,9] . The importance of the study of the LCA in pigs lies in the utilization of this species as an experimental model for cardiovascular surgery, hemodynamics, and for compared anatomy teaching -le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 12 publications
4
10
1
5
Order By: Relevance
“…The observation of most PIB ending at the cardiac apex (58%), as observed in this work, is consistent with what has been reported in elephants, rhino, pigs and humans [4,10,16,27,29,33]. In humans, short-haired sheep and pigs, the PIB has a larger calibre of the SIB.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The observation of most PIB ending at the cardiac apex (58%), as observed in this work, is consistent with what has been reported in elephants, rhino, pigs and humans [4,10,16,27,29,33]. In humans, short-haired sheep and pigs, the PIB has a larger calibre of the SIB.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, similarity was found that, in humans the calibre of the PIB is lower than in the pig and higher than in the white rhino (Table 2) [4,16,29].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…5). This observation can be accounted for by the fact that, in the pig, an accessory arterial branch originating from the distal LAD supplies the apical portions of the right ventricle [7,22]. Radioactivity measurements of noncardiac organs indicated that the highest deposition of CSCs after intracoronary infusion is in the lungs followed by liver, kidneys, and spleen.…”
Section: Discussionmentioning
confidence: 97%